This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 41. The string is ﬁxed at both ends so the resonant wavelengths are given by λ = 2L/n, where L is the length
of the string and n is an integer. The resonant frequencies are given by f = v/λ = nv/2L, where v is the
wave speed on the string. Now v = τ /µ, where τ is the tension in the string and µ is the linear mass
density of the string. Thus f = (n/2L) τ /µ. Suppose the lower frequency is associated with n = n1
and the higher frequency is associated with n = n1 + 1. There are no resonant frequencies between so
you know that the integers associated with the given frequencies diﬀer by 1. Thus f1 = (n1 /2L) τ /µ
n1 + 1 τ
= f1 +
2L µ 2L µ
This means f2 − f1 = (1/2L) τ /µ and
= 4L2 µ(f2 − f1 )2
4(0.300 m)2 (0.650 × 10−3 kg/m)(1320 Hz − 880 Hz)2
45.3 N . ...
View Full Document
- Fall '08